ENVIRONMENTAL COMMUNICATION OF INDONESIAN GOVERNMENT; CRITICAL DISCOURSE ANALYSIS ON INDONESIAN MINISTRIES SOCIAL MEDIA POSTS - Prawira, Indra; Muslikhin, Muslikhin; Riyadh, M. (Universitas Padjadjaran, 2024)
The Indonesian government is committed to preserving the global environment in the global climate summit or COP-Conference of Parties. The Government communicates its concern through social media to adapt to the massive number of social media users in Indonesia. This study aims to investigate the Indonesian Governments communication on environmental issues on social media. It adopts critical discourse analysis of Teun A Van Dijk to understand the phenomenon with data collected from published content of the Ministry of Environment and Ministry- KLHK and Ministry of State Secretary- Kemensetneg’s social media account. This study shows that those two social media accounts have low attention to environmental issues. Macrostructural analysis displays that KLHK’s social media publications focus on issues such as recycling and climate change literacy. In contrast, the Ministry of State Secretariat focuses on government policies related to environmental issues. Meanwhile, the superstructure analysis shows content that resembles mainstream media content with a cube inverted pyramid structure. The microstructure analysis shows that the content published by the two ministries targets a young audience by using non-formal language, greetings for young people, and attractive graphics and photos.